2004
DOI: 10.1051/0004-6361:20031688
|View full text |Cite
|
Sign up to set email alerts
|

VLT + UVES spectroscopy of the low-ionization intrinsic absorber in SDSS J001130.56+005550.7

Abstract: Abstract. We analyse high-resolution VLT+UVES spectra of the low-ionization intrinsic absorber observed in the BAL QSO SDSS J001130.56+005550.7. Two narrow absorption systems at velocities −600 km s −1 and −22 000 km s −1 are detected. The low-velocity system is part of the broad absorption line (BAL), while the high-velocity one is well detached. While most narrow absorption components are only detected in the high-ionization species, the lowest velocity component is detected in both highand low-ionization sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Assuming homogeneous partial coverage (Hamann & Sabra 2003), we find from these intensities that the covering factor of the absorption region is around 20% (see e.g. the relations given in Hutsemékers et al 2004). This suggests that the absorption is intrinsic to the quasar, and exterior to the BLR.…”
Section: The Intrinsic Absorption Linesmentioning
confidence: 68%
“…Assuming homogeneous partial coverage (Hamann & Sabra 2003), we find from these intensities that the covering factor of the absorption region is around 20% (see e.g. the relations given in Hutsemékers et al 2004). This suggests that the absorption is intrinsic to the quasar, and exterior to the BLR.…”
Section: The Intrinsic Absorption Linesmentioning
confidence: 68%
“…3 and 5), shows evidence for partial covering. We estimate a covering factor of ∼70% from the C iv doublet ratio using formulae given in Hutsemékers et al (2004). Finally, although the data are of lesser quality, the spectra obtained in 2015 ( Fig.…”
Section: Implications For the Quasar Structurementioning
confidence: 99%
“…The most reliable results based on BAL column densities suggest metallicity ranges between solar and ten times solar (Arav et al 2001). Previous studies of NALs in low‐redshift samples have found super‐solar metallicities and highly ionized gas, and have successfully probed several other NAL outflow characteristics (Hamann & Ferland 1999; Ganguly et al 2003; D’Odorico et al 2004; Hutsemékers, Hall & Brinkmann 2004; Ganguly et al 2006; Gabel, Arav & Kim 2006). These lower redshift samples cover a wide range of luminosities, observed in the UV spectral range, where many useful metal and hydrogen lines occur.…”
Section: Introductionmentioning
confidence: 99%